2012
DOI: 10.1371/journal.pone.0043483
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties and Mechanisms of Fucoidan on Mouse Breast Cancer In Vitro and In Vivo

Abstract: BackgroundFucoidan is a sulfated polysaccharide derived from brown algae that has been reported to perform multiple biological activities, including antitumor activity. In this study, we examined the influence of crude fucoidan on mouse breast cancer in vitro and in vivo.Materials and MethodsIn vitro, fluorescent staining, flow cytometry and Western blot were performed to analyze apoptosis and vascular endothelial growth factor (VEGF) expression of mouse breast cancer 4T1 cells. In vivo, therapy experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
142
1
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 31 publications
9
142
1
18
Order By: Relevance
“…Initiator caspases, caspase-8 and -9, are phosphorylated by a variety apoptotic signals (Kim et al 2010). Activated or cleaved caspase-3 is an essential effector for induction of apoptosis (Xue et al 2012). Previous studies' results support our hypothesis that multiple mAb P CO17-1A × BR55 meaningfully and effectively induce the apoptosis of AOM/ DSS-induced colorectal tumor than anti-EpCAM and mAb P CO17-1A.…”
Section: Discussionsupporting
confidence: 73%
“…Initiator caspases, caspase-8 and -9, are phosphorylated by a variety apoptotic signals (Kim et al 2010). Activated or cleaved caspase-3 is an essential effector for induction of apoptosis (Xue et al 2012). Previous studies' results support our hypothesis that multiple mAb P CO17-1A × BR55 meaningfully and effectively induce the apoptosis of AOM/ DSS-induced colorectal tumor than anti-EpCAM and mAb P CO17-1A.…”
Section: Discussionsupporting
confidence: 73%
“…Extracellular polymeric substance (EPS), a high molecular weight biopolymer produced via excretion, secretion, sorption and cell lysis, is a substance secreted during algal growth (6). Recent studies have shown that algal EPS has an ecological importance and exhibits numerous biological activities (7)(8)(9)(10). It has been found to have anti-thrombotic, -aging, -coagulant and -viral effects, be resistant to radiation, protect against endothelial cell damage, decrease hematic fat and blood sugar levels, regulate the immune response (7,8) and induce cell apoptosis (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Dotychczas skuteczność fukoidyny w indukcji procesu apoptozy wykazano w badaniach przeprowadzonych w modelach raka piersi, raka okrężnicy, raka płuca, czerniaka oraz chorób rozrostowych układu krwiotwórczego, takich jak szpiczak mnogi, czy białaczka limfoblastyczna [11,14,[30][31][32][33][34]. W badaniach in vitro prowadzonych przez Banafę i wsp.…”
unclassified
“…Analogiczne wyniki uzyskali Xue i wsp. (2012), którzy wykazali, że ekspozycja na fukoidynę pochodzącą z F. vesiculosus skutkuje hamowaniem proliferacji komórek mysiego raka piersi (linia 4T1), jednak nie prowadzi do spadku odsetka żywych komórek w przypadku prawidłowych ludzkich fibroblastów (linia L929) [31]. Należy zauważyć, że w opisanych badaniach wykorzystano fukoidynę wyekstrahowaną z tego samego gatunku -Fucus vesiculosus, co pozwala zakładać, że efekt przeciwnowotworowy zależny jest od zastosowanej substancji czynnej, i nie od typu nowotworu.…”
unclassified
See 1 more Smart Citation